Assessing EU Member States’ Readiness for Innovation Parks: Financial and R&D Perspectives - Tokar, Volodymyr; Tyshchenko, Dmytro; Franchuk, Tamara; Babenko, Artem; Koval, Ihor (International Journal of Economics and Financial Issues, 2025)
This article examines the readiness of EU member states to establish innovation parks by evaluating gross domestic expenditure on research and development (GERD) and the proportion of R&D personnel within the labor force. Utilizing k-means clustering, the research categorizes EU countries into three clusters based on GERD and R&D personnel metrics, allowing for a nuanced assessment of innovation potential. The analysis reveals significant disparities among EU member states, with Austria, Belgium, Denmark, Finland, Germany, and Sweden exhibiting the highest readiness for innovation parks, while others, such as Bulgaria and Romania, face substantial challenges due to limited R&D investment and workforce. This study focuses solely on GERD and R&D personnel, excluding other factors such as government policy or sectoral distinctions. Future research could integrate these elements for a more comprehensive analysis. Insights from this research can guide policymakers in tailoring interventions to enhance R&D funding and workforce development, particularly in underprepared regions. This study contributes to understanding EU innovation readiness by providing a comparative analysis based on financial and human capital, offering a novel clustering approach to assess innovation park potential across diverse EU contexts.